2012
DOI: 10.1371/journal.pone.0052251
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chemotaxis Assay in 3-D Collagen Gels by Time-Lapse Microscopy

Abstract: The directional cell response to chemical gradients, referred to as chemotaxis, plays an important role in physiological and pathological processes including development, immune response and tumor cell invasion. Despite such implications, chemotaxis remains a challenging process to study under physiologically-relevant conditions in-vitro, mainly due to difficulties in generating a well characterized and sustained gradient in substrata mimicking the in-vivo environment while allowing dynamic cell imaging. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…far before the equilibrium A c c e p t e d M a n u s c r i p t 16 regime. In support of this assumption, a recent study conducted with a chemotaxis assay similar to ours on COLI gels reported a difference between diffusivity data obtained with the semiinfinite model applied within the diffusion layer or with Finite-Element (F-E) analysis of 17% [15], which is very close to the ~15% discrepancy between our D and D FRAP values. The latter agreement suggests that the correction obtained with F-E analysis is modest, whereas it is much more computationally demanding.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…far before the equilibrium A c c e p t e d M a n u s c r i p t 16 regime. In support of this assumption, a recent study conducted with a chemotaxis assay similar to ours on COLI gels reported a difference between diffusivity data obtained with the semiinfinite model applied within the diffusion layer or with Finite-Element (F-E) analysis of 17% [15], which is very close to the ~15% discrepancy between our D and D FRAP values. The latter agreement suggests that the correction obtained with F-E analysis is modest, whereas it is much more computationally demanding.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, a less challenging approach has been reported in chemotaxis assays in which diffusivity of fluorescently labelled tracers is assessed by time-lapse fluorescence intensity measurements by fluorescence microscopy. However, these chemotaxis assays are still limited in that they require customized sample holders [15,16].…”
Section: Page 4 Of 34mentioning
confidence: 99%
See 2 more Smart Citations
“…For the molecular transport we chose to simulate the diffusion of a 10 kDa molecule with a diffusion coefficient of 2 Â 10 À6 cm 2 /s in collagen gel. 16 We assumed that the chemical concentration within the two side channels is always reported in terms of normalized values, thus varying from 0 to 1. The density and the dynamic viscosity of the fluid in the side channels were 1000 kg/m 3 and 10 À3 kg/m/s, respectively.…”
Section: Methodsmentioning
confidence: 99%